Anti- Dermatophytic Activity Study Of Essential Oil Present In Ocimum Americanum Linn (Journal of Pharmaceutical Negative Results, 2022)
The plant “Ocimum americanum” containing essential oil growing wild in Barpali, Bargarh has been studied. The essential oil from the leaves of Ocimum Americanum obtained through steam distillation were characterized for its organoleptic properties and physicochemical constants. Freshly extracted essential oil was pale yellow or slightly greenish, soluble in common organic solvents and very slightly soluble in water. Its specific gravity was 0.9071; with 1.442 as refractive index; 21.31 as optical activity and chemical constants (in % w/v) viz, acid value 2.2, ester value of 151.86, aldehyde content 76, alcohol content 40.91 and phenolic content 15. The volatile constituents of essential oil was investigated by GC MS. Twenty nine constituents were identified. The minimum inhibitory concentration (MIC) of the oil was determined using dilution method and antidermatophytic activity was tested by agar diffusion. The oil was found to have Significant antidermatophytic activity against dermatophytes such as A.varis, A.niger and P.notatum with MIC values of: 50 μg/mL, 100 μg/mL and 150 μg/mL and the average zones of growth inhibition were: 26 mm, 28 mm and 29 mm respectively.